THE INFLUENCE OF ARTIFICIAL INTELLIGENCE IN DIAGNOSTIC SYSTEMS AND HEALTHCARE WORKERS’ DIGITAL COMPETENCE ON THE EFFICIENCY OF HOSPITAL SERVICES - Astri Hindarti; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of Artificial Intelligence in diagnostic systems and the digital competence of healthcare workers on hospital service efficiency. The research employs a quantitative approach with an explanatory design to examine the causal relationships between variables. Data were collected through a structured questionnaire distributed to healthcare workers, including doctors, nurses, and administrative staff. The data were analyzed using IBM SPSS Statistics, applying validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results show that Artificial Intelligence in diagnostic systems has a positive and significant effect on hospital service efficiency. Similarly, the digital competence of healthcare workers also has a positive and significant influence on service efficiency. The simultaneous test (F-test) indicates that both variables jointly have a significant effect on hospital service efficiency. The coefficient of determination (R²) reveals that a substantial proportion of service efficiency can be explained by these two variables, while the remaining variance is influenced by other factors not examined in this study. These findings highlight that the integration of advanced technologies and the enhancement of human resource capabilities are essential in improving hospital service performance. The study suggests that hospitals should invest in the development of Artificial Intelligence systems as well as continuous training programs to strengthen the digital competence of healthcare workers. Such efforts are expected to support the achievement of efficient, effective, and high-quality healthcare services.